Implementation of the Discovery Learning Model in Islamic Religious Education Subjects - Yusup Hamdani Bakhtiar; Irawan Irawan; Tatang Muh Nasir (Al Hikmah: Journal of Education, 2025)
This research aims to determine the implementation of appropriate learning models to enhance and stimulate students' active participation in learning Islamic Religious Education, both individually and in groups. One learning method that can be used to address this issue is the application of the Discovery Learning method. This study employs a descriptive qualitative approach, focusing on students and Islamic Religious Education teachers as the research subjects. The data sources in this research consist of primary and secondary data, obtained through observations, interviews, and documentation studies. Based on the findings, it is concluded that the Discovery Learning method can be effectively applied in Islamic Religious Education to enhance and stimulate students' active and critical thinking skills, ensuring that the learning process achieves the expected outcomes. Learning with the Discovery Learning method is designed to be as engaging and enjoyable as possible for students, encouraging them to play an active role in the learning process. Furthermore, this method provides students with the opportunity to discover, process, and independently map out learning content, enabling them to better understand and master the concepts being taught. This study contributes to the field of Islamic Religious Education by demonstrating that the Discovery Learning model effectively enhances student engagement, critical thinking, and independent learning. Based on qualitative analysis conducted at SMPN 1 Kadipaten Tasikmalaya, the findings provide empirical evidence that discovery based learning not only improves academic achievement but also fosters a more enjoyable and student-centered classroom environment.